Thermal tuning of terahertz metamaterial absorber properties based on VO2. Issue 15 (31st March 2022) - Zheng, Zhipeng; Luo, Yao; Yang, Hua; Yi, Zao; Zhang, Jianguo; Song, Qianjv; Yang, Wenxing; Liu, Chao; Wu, Xianwen; Wu, Pinghui
Abstract : A novel, structurally simple, multifunctional broadband absorber is presented. The temperature control allows flexible adjustment of the absorption intensity from 0 to 0.999. When the vanadium dioxide is in its metallic state, the absorber achieves near-perfect absorption (>97%) in the ultra-broadband range of 3.7 THz–9.7 THz. Abstract : We present a novel, structurally simple, multifunctional broadband absorber. It consists of a patterned vanadium dioxide film and a metal plate spaced by a dielectric layer. Temperature control allows flexible adjustment of the absorption intensity from 0 to 0.999. The modulation mechanism of the absorber stems from the thermogenic phase change properties of the vanadium dioxide material. The absorber achieves total reflection properties in the terahertz band when the vanadium dioxide is in the insulated state. When the vanadium dioxide is in its metallic state, the absorber achieves near-perfect absorption in the ultra-broadband range of 3.7 THz–9.7 THz. Impedance matching theory and the analysis of electric field are also used to illustrate the mechanism of operation. Compared to previous reports, our structure utilizes just a single cell structure (3 layers only), and it is easy to process and manufacture. The absorption rate and operating bandwidth of the absorber are also optimised. In addition, the absorber is not only insensitive to polarization, but also very tolerant to the angle of incidence. Such a design would have great potential in wide-ranging applications, including photochemical energy harvesting, stealth devices, thermal emitters, etc.